Training to increase personal potential through achievement motivation for the Inline Skate Community, Purworejo - Patria Jati Kusuma; Jihan Fauziah Fatwa; Nindya Nada Perkusi; Zazkia Anzalna Lasifa; Putri Julia Prastiwi (Community Empowerment, 2024)
The main objective of this activity is to increase the achievement motivation of members of the Purworejo inline skate community through structured training. Additionally, this activity aims to hone participants' interests and talents, as well as build their self-confidence. The methods used in this activity include lectures, discussions, and assessments. Assessments were conducted before and after training using Google Forms containing pre-tests and post-tests to measure changes in participants' understanding and motivation. The results of the training showed a significant increase in participants' understanding of their potential and achievement motivation. This inline skate training activity successfully increased participants' achievement motivation and self-confidence. Furthermore, these results highlight the importance of the role of parents and teachers in supporting the development of children's potential by understanding each child's learning style.